2022
DOI: 10.1101/2022.01.16.476016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mucociliary Transport Deficiency and Disease Progression in Syrian Hamsters with SARS-CoV-2 Infection

Abstract: Substantial clinical evidence supports the notion that ciliary function in the airways plays an important role in COVID-19 pathogenesis. Although ciliary damage has been observed in both in vitro and in vivo models, consequent impaired mucociliary transport (MCT) remains unknown for the intact MCT apparatus from an in vivo model of disease. Using golden Syrian hamsters, a common animal model that recapitulates human COVID-19, we quantitatively followed the time course of physiological, virological, and patholo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 76 publications
0
14
2
Order By: Relevance
“…Since we observed that these treatments did not impair SARS-CoV-2 replication in vitro , we hypothesize that neutrophils may have a counterproductive effect by releasing infected cells into the lumen of the nasal cavity. These infected cells could allow the virus to spread more easily in the nasal cavity due to impairment of mucociliary clearance that has been recently shown to be reduced during SARS-CoV-2 infection ( 53 ). Such a hypothesis is consistent with our results showing that cyclophosphamide and IcatC XPZ-01 treatment significantly reduced the amount of infected desquamated cells filling the lumen of the nasal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Since we observed that these treatments did not impair SARS-CoV-2 replication in vitro , we hypothesize that neutrophils may have a counterproductive effect by releasing infected cells into the lumen of the nasal cavity. These infected cells could allow the virus to spread more easily in the nasal cavity due to impairment of mucociliary clearance that has been recently shown to be reduced during SARS-CoV-2 infection ( 53 ). Such a hypothesis is consistent with our results showing that cyclophosphamide and IcatC XPZ-01 treatment significantly reduced the amount of infected desquamated cells filling the lumen of the nasal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted July 11, 2022. ; https://doi.org/10.1101/2022.07.08.499336 doi: bioRxiv preprint tracheobronchial epithelial (HTBE) cells (7,10,29), nasal ciliated cells from human and non-human primates (5), Syrian hamsters (11,30,31), and SARS-CoV-2 infected human nasal organoids. (32) In addition, diminished mucociliary clearance by SARS-CoV-2 has been demonstrated in HTBE cells by tracking polystyrene beads (10) and in Syrian hamsters by µOCT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pCC was not affected by the duration of illness (R 2 <0.01). (Figure S1) SARS-CoV-2 infection in experimental animals and in vitro is known to cause shortening and misshapen ciliary structure, thus contributing to alterations in function (10,11), but this has not yet been assessed in symptomatic COVID-19 patients. µOCT demonstrated ciliary beat frequency was severely diminished in COVID-19 patients compared to controls (12.32 ± 2.58 Hz healthy controls vs 7.57 ± 2.56 Hz COVID-19, P= 0.011).…”
Section: Covid-19 Leads To Severe Loss Of Ciliary Coverage In the Nas...mentioning
confidence: 99%
See 2 more Smart Citations